Effect of anisotropy and texture on the low cycle fatigue behavior of Inconel 718 processed via electron beam melting. (December 2017) - Kirka, M.M.; Greeley, D.A.; Hawkins, C.; Dehoff, R.R.
Highlights: LCF behavior of columnar and equiax grain EBM Inconel 718 is examined. LCF performance of EBM Inconel 718 comparable to wrought Inconel 718. Columnar grains parallel to build direction fails through intergranular cracking. Columnar grains transverse to build direction fails through transgranular cracking. Equiax grains fails through intergranular and transgranular mechanisms. Abstract: In this study, the impact of texture (columnar/equiax grain structure) and influence of material orientation on the low cycle fatigue (LCF) behavior of hot isostatic pressed (HIP) and heat-treated Inconel 718 fabricated through electron beam melting (EBM) is investigated. Material was tested both parallel and perpendicular (transverse) to the build direction. In all instances, the EBM HIP and heat-treated Inconel 718 performed similarly or exceeded the LCF life of wrought Inconel 718 plate and bar stock under fully reversed strain-controlled loading at 650 °C. Amongst the textures, the columnar grains oriented parallel to the build direction exhibited the highest life on average compared to the transverse columnar and equiax EBM material. Further, in relation to the reference wrought material the parallel columnar grain material exhibited a greater life. While a negligible life difference was observed in the equiax grained material between the two orientations, a consistently lower accumulated inelastic strain was measured for the material loaded parallel to the build direction than the transverse orientation. Failure of the parallel columnar material occurred in a transgranular manner with cracks emanating from the surface whereas the transverse columnar material failed in a intergranular manner, with crack growth occurring through repeated rupture of oxide at the crack-tip. In the case of the equiax material, an influence of material orientation was not observed on the failure mechanism with crack propagation occurring through a combination of debonded/cracked carbides and void formation along twin boundaries resulting in a mixture of intergranular and transgranular crack propagation.